Earnings Management, CSR Disclosure, and Firm Value: The Moderating Role of Audit Quality - Lia Fatmasari; Nurcahyono Nurcahyono (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Financial and non-financial factors are widely recognized as key determinants of firm value in emerging markets, yet empirical evidence on the roles of earnings management and Corporate Social Responsibility (CSR) disclosure remains inconclusive. This study examines the effects of earnings management and CSR disclosure on firm value, with audit quality as a moderating variable, using a sample of 268 firm-year observations of non-cyclical consumer firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Moderated Regression Analysis (MRA) is employed to test both direct and interaction effects. The results indicate that earnings management has a significant negative effect on firm value, suggesting that greater managerial opportunism reduces investor confidence and market valuation. In contrast, CSR disclosure does not significantly affect firm value, implying that it has not yet become a relevant signal for investors in this sector. Furthermore, audit quality attenuates the negative impact of earnings management by enhancing the credibility of financial reporting, but does not moderate the relationship between CSR disclosure and firm value. These findings underscore the importance of high-quality audits in strengthening reporting credibility and shaping investor responses in emerging markets.